The relationship between innovative performance and environmental regulations: Evidences from Jiangsu Province, China - Duan, Jingjing; Xia, Shiliang (Frontiers in Environmental Science, 2022)
With the endless constraints brought about by limited resources and increased pollution, practices that aim for sustainable and innovative development is often seen as the thing of the future. Despite this collective shift towards sustainability, the relationship between regional innovation and environmental protection still vastly differs between different geographic units. This paper takes the Jiangsu province, a pioneering economic zone in East China, as a study object, and uses its thirteen cities’ panel data from 2006 to 2020 to check human capital input, foreign direct investment, research and development fund input, environmental pollution, and other independent variables that influence its innovation output. The study finds a strong positive relationship between R&D investment of enterprises, human capital input, local loans scaled for technical innovation, environmental regulation and innovative output. while the same is untrue between research and development fund input from government and innovative output. There are also negative contribution from the openness of cities and foreign direct investment, which indicates that presently more innovative achievements in Jiangsu come from independent research and development rather than relying on technology spillovers from foreign direct investments. Finally, future policies about enhancing the research and development input scale, encouraging local human capital, executing more fiscal and direct capital supporting tools, and upholding liberal trade policies as high-quality international export-oriented economy are suggested.